DAMPAK ANISOMETROPIA TINGGI YANG TIDAK TERKOREKSI PADA MATA DAN PENANGGULANGANNYA - Misnawati; Nisa Zakiati Umami (Akademi Refraksi Optisi dan Optometry Gapopin, 2021)
Refraction error such as myopia, hypermetropia and astigmatism with a difference significant diopters are now experienced by a small part of people. That refraction error called anisometropia is caused by many things, such as predetermined at birth, trauma, and even the failure of surgery refraction. On the patient's anisometropia, refraction examination is done by using special Test FRIEND or a test Worth Four Dot. The author uses descriptive method of data libraries, including the essay from Troy E. Fannin, O.D. and Theodore Grosvenor, O.D., Ph.d., titled